2015
DOI: 10.1002/andp.201400189
|View full text |Cite
|
Sign up to set email alerts
|

Non‐equilibrium dynamics in dissipative Bose‐Hubbard chains

Abstract: Open many-body quantum systems have recently gained renewed interest in the context of quantum information science and quantum transport with biological clusters and ultracold atomic gases. We present a series of results in diverse setups based on a Master equation approach to describe the dissipative dynamics of ultracold bosons in a one-dimensional lattice. We predict the creation of mesoscopic stable many-body structures in the lattice and study the non-equilibrium transport of neutral atoms in the regime o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 62 publications
1
63
0
Order By: Relevance
“…This system without collisional dephasing has previously been analyzed by Penna [13], in what he named the central depleted well regime. Aspects of a similar system have also been analyzed by Kordas et al [14], who found that phase diffusion could enhance tunneling and damp coherent oscillations in the tunneling. Kordas and others have also analyzed the influence of atomic losses on a Bose-Hubbard system, outlining various useful theoretical approaches [15].…”
Section: Introductionmentioning
confidence: 92%
“…This system without collisional dephasing has previously been analyzed by Penna [13], in what he named the central depleted well regime. Aspects of a similar system have also been analyzed by Kordas et al [14], who found that phase diffusion could enhance tunneling and damp coherent oscillations in the tunneling. Kordas and others have also analyzed the influence of atomic losses on a Bose-Hubbard system, outlining various useful theoretical approaches [15].…”
Section: Introductionmentioning
confidence: 92%
“…Although the results reported here are explained qualitatively within the framework of Gutzwiller meanfield theory for density matrices and Lindblad master equation, it would be desirable in future to verify it using more sophisticated tools like truncated Wigner approximations [47], quantum trajectories method [48] or by constructing density matrix using exact diagonalization techniques, alleviating the limitations of GMFT. A natural extension of the study presented here would be to explore dissipative dynamics in disordered systems, and in particular, the Bose glass phase.…”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, we explicitly test the robustness of our scheme against dynamical environmental effect, specifically dephasing due to spontaneous emission, which represents the main source of decoherence in optical lattices. The dynamics of the system in the lowest band is typically modeled as a Master equation in Lindblad form [65][66][67]:…”
Section: Environmental Effectsmentioning
confidence: 99%